Penerapan Model Discovery Learning Berbantuan E-Worksheet Untuk Meningkatkan Hasil Belajar Materi Turunan Fungsi Aljabar - Wuwur, Elisa Gaudensia (Universitas Nusa Cendana, 2025)
Based on the interview results, student learning outcomes at SMAN 3 Kupang for algebraic function derivative material are low, which is just about 50% students passing the semester test. Students have difficulty in understanding the material from the book, and only some students are active in giving responses. This study aims to improve the learning outcomes of algebraic function derivative material in class XI MIPA SMAN 3 Kupang by using the Discovery Learning model assisted by eworksheet to make students become more active and the learning process becomes more interesting. This research is a class action research and the subjects are 36 students class XI MIPA 1 and researchers as teachers. The results showed that student learning outcomes had improved, shown by the presentation of classical completeness which is 62.5% in cycle I and increased to 87.5% in cycle II. The percentage of teacher activity is 91.67% in cycle I became 93.75% in cycle II and it is in the very good category. The percentage of student activity is 84.38% in cycle I became 85.98% in cycle II and it is in the good category so it can be concluded that the discovery learning model assisted by eworksheet can improve the learning outcomes of algebraic function derivative material in class XI MIPA SMAN 3 Kupang.